The essence and theoretical characteristics of competition in livestock - Perehuda, Yuliia (Management and Entrepreneurship: Trends of Development, 2023)
The article is dedicated to forming new scientific solutions regarding defining the essence and providing theoretical characteristics of competition, including livestock products. It has been proven that under conditions of the transition to a post-industrial type of economy, it is essential for Ukraine to ensure the competitiveness of the critical sectors of the economy, namely the agricultural sector, and its components, especially those that have problems in competitiveness, such as livestock. The article aims to define the essence of the terms "competition," "competition in the agricultural sector," and "competition in livestock" and provide a theoretical description of the competition, including one in livestock, based on a comparative assessment of the foreign and domestic scientists scientific achievements and legislative and regulatory documents of Ukraine. Methodology: a set of general and special methods has been used at the empirical and theoretical levels, such as methods of literary analysis and the use of Frege's semantic triangle to determine the essence of the terms "competition," "competition in the agricultural sector," "competition in livestock," "competitive advantage"; comparative assessment to identify the main features of competition regarded as a scientific category and economic phenomenon (process); methods of logical generalization and scientific abstraction to determine the components of the theoretical characteristics of competition; methods of system analysis and synthesis to form a hierarchical set of competition levels; methods of systematization, grouping and logical generalization for information systematization, drawing conclusions and scientific proposals of the article. The article uses system and functional, historical, and systemic approaches in revealing and solving the problem of defining the essence and providing a theoretical characterization of competition in livestock. Results: the author's definition of the terms "competition," "competition in the agricultural sector," and "competition in livestock" has been provided, and three components of competition, including that in livestock, have been revealed: economic entities, competition levels, and competitive advantages.JEL Classification: D21, Q12.